PENGETAHUAN, SIKAP DAN PERILAKU MASYARAKAT YANG BERKAITAN DENGAN PENYAKIT TUBERKULOSIS (TB) PARU DI PUSKESMAS KOTO KATIK KOTA PADANG PANJANG (SUMATERA BARAT) - Media, Yulfira (Publikasi Penelitian Terapan dan Kebijakan, 2011)
Tuberculosis (TB) Paru is still one of the major health problems in West Sumatera. Research knowledge, attitudes and behavior associated with pulmonary TB have been conducted in health centers Katiak Koto, city of Padang Panjang in 2012. The purpose of this study was to determine knowledge, attitudes and behavior associated with pulmonary tuberculosis. Research is conducted with a qualitative approach, data collection was done through indepth interview and Focus Group Discussion (FGD) with several informants such community leaders, patients, traditional health provider, and caders. The results showed that their knowledge of TB disease is relatively good. However, some other people still think that the cause of pulmonary TB disease wasrelated to things that are supernatural / magic and because of heredity. The perception that most people who experienced disease is the common cold, it affects the appearance of a lack of caring from the community to the effect that can be caused by pulmonary TB disease. Behavior and awareness of some people to check their sputum and use of health care facilities are still lacking, because they are ashamed and afraid sentenced to suffer from pulmonary tuberculosis.